Colloid Carcinoma of the Pancreas: A Distinct Pancreatic Neoplasm with Good Prognosis. Report of a Case - Rubio-Perez, Ines; Martin-Perez, Elena; Sanchez-Urdazpal, Luis; Corbaton, Paloma; Larrañaga, Eduardo (JOP. Journal of the Pancreas, 2012)
<!–[if gte mso 9]> Normal 0 14 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –> Context: Colloid carcinoma is considered a distinct type of pancreatic neoplasia with specific histopathological and molecular features, and a better prognosis. Case report We present the case of a patient with a 15cm locally invasive colloid carcinoma of the pancreas, in which an aggressive surgical approach achieved no evidence of disease 24 months after surgery. Conclusions If an accurate diagnostic approach and surgical resection are performed, the 5-year survival rate can reach 60%. Presence of invasive intraductal papillary mucinous neoplasm has been reported, and this can affect the prognosis. Adjuvant therapy has not demonstrated improvement of survival in surgically-resected patients.